PENGIRIMAN DATA NRF24L01+ DENGAN KONDISI LINE OF SIGHT DAN NON LINE OF SIGHT - I Gusti Made Ngurah Desnanjaya; Mohammad Dwi Alfian (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2020)
Wireless Sensor Network is a wireless network technology that includes sensor nodes and embedded systems. WSN has several advantages: it is cheaper for large-scale applications, can withstand extreme environments, and data transmission is relatively more stable. One of the WSN devices is nRF24L01+. Within the specifications given, the maximum communication distance is 1.1 km. However, the most effective distance for transmitting data in line of sight and non-line of sight is still unknown. Therefore, testing and analysis are needed so that the nRF24L01+ device can be used optimally for communication and data transmission. Through testing analysis on nRF24L01+ line of sight, Kuta beach location in Bali and non-line of sight on the STMIK STIKOM Indonesia campus. The effective communication distance of the nRF24L01+ module in line of sight is between 1 and 1000 meters. The distance of 1000 meters is the limit of the effective distance for sending data, and the packet loss rate is less than 15% which is included in the medium category. Meanwhile, in the non-line of sight, the effective distance of the nRF24L01+ communication module is 20 meters, and the packet loss is close to 15%, which is a moderate level limit. With the analysis module, nRF24L01+ can be a reference in determining the effective distance on WSN nRF24L01+ in determining remote control equipment data communication.